2004
DOI: 10.1149/1.1640628
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Electrolyte Fuel Cells Based on Phosphoric Acid-Impregnated Poly(2,5-benzimidazole) Membranes

Abstract: Preparation and characterization of membranes of poly͑2,5-benzimidazole͒ ͑ABPBI͒ ͑as thin as 20 m͒ for polymer electrolyte membrane fuel cells are reported. These membranes were prepared by solution casting and then impregnated in phosphoric acid baths. Their characterization included thermogravimetric analyses, conductivity measurements, Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. These membranes have high thermal stability and good proton conductivity at temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
192
2
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(215 citation statements)
references
References 24 publications
13
192
2
8
Order By: Relevance
“…Lithium chloride was used to enhance the dissolution of the product in DMF. [24]. The bands around 3400 cm À1 in PSf-BIm are attributed to the isolated N-H stretching.…”
Section: Resultsmentioning
confidence: 94%
“…Lithium chloride was used to enhance the dissolution of the product in DMF. [24]. The bands around 3400 cm À1 in PSf-BIm are attributed to the isolated N-H stretching.…”
Section: Resultsmentioning
confidence: 94%
“…used in the pharmaceutical industry) and non-carcinogenic. Recent efforts to synthesize AB-PBI are made in polyphosphoric acid [13,15,94,95] or in a P 2 O 5 -MSA mixture [84]. As the unbalancing of stoichiometry is avoided, the synthesis would be less demanding for the purity of the monomer.…”
Section: Ab-pbimentioning
confidence: 99%
“…As the unbalancing of stoichiometry is avoided, the synthesis would be less demanding for the purity of the monomer. It is, however, reported that the high purity monomer gives polymers of high molecular weights [13,95]. By using recrystallized DABA, Wainright et al [13] synthesized AB-PBI with an inherent viscosity as high as 7.33, which is essential to prepare PBI membranes by direct casting (see Section 2.2.1) from a PBI solution in trifluoroacetic acid (TFA)-PA mixture.…”
Section: Ab-pbimentioning
confidence: 99%
“…At 130 °C, Pt based catalysts tolerate 1000 ppm CO 2 , 2 while at 80 °C CO concentrations between 10-20 ppm are enough to cause a significant loss in the cell performance. Conventional Nafion ® membranes do not allow operation at temperatures higher than 80 o C. The search for electrolytes that can be used at higher temperatures and also low relative humidity is an active area of investigation nowadays, and promising examples are the phosphoric acid doped PBI 3,4 or ABPBI 5,6 membranes. The proton conductivity of phosphoric acid in doped membranes increases with increasing temperature and acid concentration, and with relative humidity due to the interaction of water with excess acid.…”
Section: Introductionmentioning
confidence: 99%